Microstructure and electronic structure of Cr2C and Fe2Y in the Cr-coating prepared by pack-cementation on the surface of ODS steel. (September 2021) - Hou, Xiang; Wang, Hao; Liu, Yixiang; Shu, Ming; Hu, Jianjun; Chai, Linjiang; Song, Bo; Guo, Ning; Guo, Shengfeng
Abstract: In this study, a combination of experimental characterization and first-principles calculation was employed to systematically study the structure and electronic properties of Cr-coating prepared on the surface of oxide dispersion strengthened (ODS) steel by pack-cementation chromizing. X-ray diffraction (XRD) and energy dispersive spectrometer (EDS) results show that the Cr-coating is mainly composed of Cr2 C and Fe2 Y phases. The first-principles calculation results show that the Cr atoms and C atoms in the Cr2 C crystal are bonded by ionic bonds, while the Fe atoms and Y atoms in the Fe2 Y crystal are mainly boned by polar covalent bonds. Compared with Fe2 Y, Cr2 C crystal has greater elastic anisotropy. The elastic constant of Cr2 C crystal increases significantly with the increase of pressure. When the pressure reaches 2.4 GPa, Cr2 C undergoes a transition from ductile to brittle. The elastic modulus of Fe2 Y increases slowly with increasing pressure, and always appears as a ductile phase under the pressure value of 0–6 GPa, which is considered to have a good effect on the impact properties of the Cr-coating. The average work function of Cr2 C crystal electrons is greater than that of Fe2 Y crystal electrons, indicating that when the coating is in a corrosive medium, the Fe2 Y phase will serve as the anode in the electrode first, and will be corroded before the Cr2 C phase.